Analisis Persepsi Mahasiswa Terhadap Penggunaan Quizizz Sebagai Evaluasi Hasil Belajar disertai Asessment Online - Novike Bela Sumanik; John Yoro Parlindungan; Gardis Andari; Lamtiar Ferawati Siregar (Faculty of Teacher Training and Education, Musamus University, 2021)
The COVID-19 pandemic has caused the learning process to change, from face-to-face to online learning. Online learning requires optimal mastery of technology and the need for innovation in learning, especially in evaluating learning outcomes and online assessment. The use of Quizizz media is an alternative for evaluation with an attractive appearance far from being scary. This study uses a quantitative descriptive method that aims to determine student perceptions of the evaluation of learning outcomes accompanied by online assessment using Quizziz media. The research subjects are active students of chemistry education, Musamus University who have participated in an evaluation using quizizz. The instrument of this research is a questionnaire containing 20 questions based on 6 indicators and using a Likert scale. The research data was obtained from the results of the questionnaire that had been distributed through the google form application. The results showed that students' perceptions of the use of quizizz received a positive response of 87%. The conclusion in this study is that the use of quizizz as an evaluation accompanied by online assessment can be applied in chemistry education and can increase student motivation in learning.